2019
DOI: 10.1016/j.jss.2018.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and Communication in the Operating Room

Abstract: Background: Poor communication is implicated in many adverse events in the operating room (OR); however, many hospitals' scheduling practices permit unfamiliar operative teams. The relationship between unfamiliarity, team communication, and effectiveness of communication is poorly understood. We sought to evaluate the relationship between familiarity, communication rates, and communication ineffectiveness of healthcare providers in the OR. Materials and Methods: We performed purposive sampling of 10 open opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Captured issues in this category include: lack of effective communication and interaction between care providers, 48,5256,58 a shift change without clear communication, 48,51,53,59 unfamiliarity of surgery team with each other, 65 and poor teamwork. 63,65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Captured issues in this category include: lack of effective communication and interaction between care providers, 48,5256,58 a shift change without clear communication, 48,51,53,59 unfamiliarity of surgery team with each other, 65 and poor teamwork. 63,65…”
Section: Resultsmentioning
confidence: 99%
“…After careful analysis, we determined that this trait influences the following contributing causes of URFOs: 1) lack of role clarity 48 (under the main category of lack of policies and procedures) and ineffective communication policies 51 from the Government and Regulatory Bodies layer, 2) ineffective communication; i.e. culture of poor communication 48 from the Company layer, 3) presence of multiple surgical teams in ORs 48,54,59 (under the work environment main category) from the Management layer, and 4) communication breakdown and lack of co-operation 48,5156, 59,63, 65 from the Staff layer. Integrating the 10 traits of a positive safety culture with the AcciMap framework, which systematically captures and analyzes the contributing causes of URFOs across its hierarchical layers, enabled us to identify instances of violations across safety culture traits and understand the consequences of those violations on OR operations; i.e.…”
Section: Resultsmentioning
confidence: 99%
“…4,17,18,44 Objective and fair assessment of clinical performance in the perioperative setting is critical for focused education, meaningful feedback and incentives, and for HSS. Both under-and overutilization can be evaluated with our metric, for example to (1) investigate perioperative clinician dyads (attending/resident, attending/nurse anesthetist), 56 (2) explore the impact of CDS on risk-adjusted utilization of resources, [57][58][59] or (3) evaluate clinician, team, and/or institutional improvements in enhancing value or adherence to guidelines, 22 and (4) report quality measures to P4P programs that are relevant to the scope of practice of anesthesiologists and linked to outcomes. 17…”
Section: Discussionmentioning
confidence: 99%
“…According to MST, the familiarity of individuals with the duties or activities they are supposed to be performing will affect the relative amounts of convergence and conveyance. Frasier et al (2019) showed that familiarity and communication will influence each other. We therefore propose the following:…”
Section: Media Synchronicity Theorymentioning
confidence: 99%